please solve this
![\cos( ^{6} ) a + \sin(^{6} ) a = 1 - 3 \sin( ^{2} ) \cos(^{2} ) a \cos( ^{6} ) a + \sin(^{6} ) a = 1 - 3 \sin( ^{2} ) \cos(^{2} ) a](https://tex.z-dn.net/?f=+%5Ccos%28+%5E%7B6%7D+%29+a+%2B++%5Csin%28%5E%7B6%7D+%29+a+%3D+1+-+3+%5Csin%28+%5E%7B2%7D+%29++%5Ccos%28%5E%7B2%7D+%29+a)
pls don't mess its important
Answers
Answered by
1
Answer:
L.H.S. = cos⁶a + sin⁶a
= (cos²a + sin²a) (cos⁴a - sin²a cos²a + sin²a)
= (sin⁴a + cos⁴a) - sin²a cos²a
= 1 - 2sin²a cos²a - sin²a cos²a
= 1 - 3sin²a cos²a
= R.H.S.
Hence proved.
Similar questions